ISU-ISU PEMENUHAN HAK PELAYANAN KESEHATAN BAGI WARGA BINAAN LANJUT USIA - Shafiq, Mitsal (Journal of Correctional Studies, 2025)
This article aims to explore crucial issues related to fulfilling the right to health services for elderly residents. In an effort to achieve a deeper understanding, this article will discuss several important aspects, including the often limited access, the quality of health services they receive, the impact of social isolation and emotional well-being on this population, as well as the role of government policy and possible system reforms in improving their health services. Thus, this article aims to provide a comprehensive and thorough view of the challenges and solutions related to fulfilling the right to health services for elderly residents